Aspectos morfológicos e microanatômicos das espécies brasileiras de Mussidae Ortmann, 1890 (Cnidaria, Scleractinia) - Pitombo, Fabio Bettini (1992)
In the purpose of extend the character used in Scleractinian systematic, it was done a descriptive study of different aspects of the polyp microanatomy and cnidom of four species of Mussidae. Three species belonging to the Brazilian genus Mussismilia: M. hispida (Verrill, 1868), M. braziliensis (Verrill, 1868) and M. hartti (Verrill, 1902) and one from the world wide genus Scolymia Haime, 1852: S. wellsi. The microanatomical study allowed a more ample characterization of the species, and also revealed new characters that can be used in the systematic of the group: the form and distribution of the mesogleal pleats where the retractor muscle is fixed; the number of perfect mesenteries; distribution of the reproductive elements; the presence of linkage between the stomodaeum. The cnidae of four species of Mussidae was described and illustrated. Both Weill's (1934) cnidae nomenclature, later modified by Carlgren (1940), and Schmidt's (1969, 1972, 1974) were used. Qualitative analysis of their cnidae showed that all the species studied present the same types and distributions of nematocysts. Five types were observed (sensu Schmidt): spirocysts, holotrichs I, holotrichs II, b-rhabdoids, and p-rhabdoids D. Some types presented morphological varieties considered as subtypes. Qualitative and quantitative size analysis of cnidae showed differences between Mussismilia and Scolyia. The qualitative difference observed was that Mussismilia presenta two size classes of. p-rhabdoids D in the mesenterial filaments, while in Scolymia there is only one. Statistical tests suggested that the size of three types of nematocysts can differentiate the two genera studied: b-rhabdoids from stomodaeum and holotrichs I and II from the mesenterial filamente. A structure was described at the extremities of the filaments, it may be related to territorial or aggressive patterns.